Pembuatan Biodiesel Dari Minyak Biji Kapuk (Ceiba Pentandra) Dengan Katalis Lempung Teraktivasi; Pengaruh Waktu Reaksi Terhadap Yield Biodiesel - Nurlis Nurlis; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Research on production biodiesel from kapok seed oil (ceiba pentandra) using an activated clay catalyst has been performed. It aimed to determine the effect of an activated clay catalyst on producing biodiesel, its quality and to study the effect of reaction time. Clay catalyst was activated by H2SO4 0.47%, 0.62%, 0.78% and NaOH with a concentration of 0.33%, 0.44%, 0.66%. Esterification with methanol in the ratio 1:12 with the addition of H2SO4 as much as 1% of the weight of oil. The next transesterification reaction, the kapok seed oil is reacted with methanol in the ratio of 1: 9 with the acids and bases activated clay catalyst. The reaction temperature of 60 °C, various of reaction time 1 hour, 1.5 hours and 2 hours. The results showed that the use of an activated clay catalyst H2SO4 0.78%, the reaction time of 1.5 hours to produce the highest yield 92.18%. Physical characteristics of biodiesel were obtained density 869 kg/m3, kinematic viscosity of 2.67 cSt, the acid number of 0.45 mg KOH/g sample and the flash point of 209oC. From the results was obtained biodiesel produced in compliance with the SNI 7182: 2015.Keywords: activation, biodiesel, clay, kapok seed oil, transesterification